Design, Synthesis, and Mechanistic Anticancer Evaluation of New Pyrimidine-Tethered Compounds - Farida Reymova; Belgin Sever; Edanur Topalan; Canan Sevimli-Gur; Mustafa Can; Amaç Fatih Tuyun; Faika Başoğlu; Abdulilah Ece; Masami Otsuka; Mikako Fujita; Hasan Demirci; Halilibrahim Ciftci (Pharmaceuticals, 2025)
Background: Despite recent breakthroughs in cancer treatment, non-small cell lung cancer (NSCLC) and breast cancer remain major causes of death from all malignancies. The epidermal growth factor receptor (EGFR) is an important mediator of the pathways involved in cell proliferation, apoptosis, and angiogenesis. Thus, its overexpression triggers several types of cancer, including NSCLC and breast cancer. Methods: In the current study, we synthesized new pyrimidine-tethered compounds (chalcone derivative (B-4), pyrazoline–carbothioamide (B-9), and pyrazoline–thiazole hybrids (BH1-7)). These compounds were then tested for cytotoxicity against A549 NSCLC and MCF-7 breast cancer cells. Results: Of these, B-4 displayed significant cytotoxicity against both cells (IC50 = 6.70 ± 1.02 µM for MCF-7; IC50 = 20.49 ± 2.7 µM for A549) compared to the standard agent lapatinib (IC50 = 9.71 ± 1.12 µM for MCF-7; IC50 = 18.21 ± 3.25 µM for A549). The anticancer potential of B-4 between Jurkat leukemic T cells and peripheral blood mononuclear cells (PBMCs) (healthy) was found to be selective. Mechanistically, 11.9% and 10.2% of A549 and MCF-7 cells treated with B-4, respectively, underwent apoptosis and B-4 produced 46% EGFR inhibition at a concentration of 10 μM. The B-4/EGFR complex obtained after induced fit docking was subjected to 300 ns of molecular dynamics simulation, which confirmed the stability of the complex in a mimicked biological environment. On the other hand, B-4 was shown to have drug-like properties by in silico pharmacokinetic estimation. Conclusions: B-4 is an EGFR inhibitor and apoptosis inducer for future NSCLC and breast cancer studies.